The Effect of Heavy Bag Thrust And Battle Rope Exercise On Arm Muscle Power And Shot Put Results of Female Shot Put Athletes Dumpang Athletics Club 2025 (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to evaluate the combined effects of heavy bag thrust and battle rope exercises on arm muscle strength and shot put performance in female athletes from the Dumpang Athletics Club. This is important because it could contribute to the advancement of science and technology in Indonesian sports, ultimately improving athlete performance. The approach used was an experimental design with a single-group pre-test and post-test. Eight athletes participated in six weeks of training sessions. Their performance was assessed before and after training to gauge the effectiveness of the intervention. The results showed a significant increase in arm muscle strength, as evidenced by the calculated t-value (11.729), which was greater than the t-value (1.895). The same increase was also seen in shot put performance, where the calculated t-value (11.336) was higher than the t-value (1.895), with both results at the 0.05 significance level. It can be concluded that the combination of heavy bag thrust and battle rope exercises significantly increased arm muscle strength and shot put performance in athletes. It is hoped that the results of this study will be a consideration for coaches and clubs in designing more effective training programs to improve athletes' basic abilities.